The Effect of Water Type on the Growth of Mung Bean Sprouts for Six Days - Zakaria, Arjun Dwi; Pratama, Bagas Yoga (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Green beans (*Vigna radiata L.*) are an important food crop that has high nutritional value and is easy to cultivate. This research aims to analyze the effect of water type (well water, rice washing water, and rainwater) on the growth of green bean sprouts for six days. Green bean seeds are soaked in the three types of water for five hours before being planted in soil. Parameters observed included plant height and time of first leaf appearance. The results showed that the type of water had a significant influence on the growth of sprouts. Rice washing water produced the highest average sprout height, followed by well water, while rainwater gave lower results. In addition, the emergence of the first leaves occurred more quickly in sprouts soaked in rice washing water compared to other types of water. The nutritional content in rice washing water, such as carbohydrates and vitamins, is thought to have a positive effect on plant growth. This research concludes that rice washing water is the most effective choice for supporting the growth of green bean sprouts during the initial phase. These findings can provide practical guidance in utilizing water resources for sustainable agriculture, especially in regions that face limited access to quality water. Keywords: green beans, types of water, sprout growth, rice washing water, sustainable agriculture